Hubungan antara Gaya Kepemimpinan dengan Motivasi Kerja Karyawan - Putri Amanda Shalsadila; Erik Setiawan (UNISBA Press, 2024)
Abstract. It cannot be denied that communication is important for humans and organizations. Without communication within an organization, it is very likely that any activities carried out will not be carried out according to the plans that have been determined. There are many components needed in managing an organization, one of which is leadership which can unite all elements to work together to achieve organizational goals. In carrying out work, a leader applies various leadership styles. The existence of a leadership style is often considered an important factor in determining the success or failure of an organization. A leadership style that focuses on tasks rather than employees can cause subordinates' work motivation to decrease. On the other hand, a leadership style that focuses more on subordinates can increase subordinates' work motivation. This is the background for researchers to conduct research on